2020
DOI: 10.1182/bloodadvances.2020001758
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived extracellular vesicles infiltrate and modify the bone marrow during inflammation

Abstract: Abstract During inflammation, steady-state hematopoiesis switches to emergency hematopoiesis to repopulate myeloid cells, with a bias toward the megakaryocytic lineage. Soluble inflammatory cues are thought to be largely responsible for these alterations. However, how these plasma factors rapidly alter the bone marrow (BM) is not understood. Inflammation also drives platelet activation, causing the release of platelet-derived extracellular vesicles (PEVs), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 60 publications
1
67
0
Order By: Relevance
“…In addition to direct virus interaction with megakaryocytes and platelets, it is possible SARS-CoV-2 virus released into extracellular vesicles from infected white blood cells or endothelial cells can be internalized by platelets, resulting in SARS-CoV-2 virus positive platelets through indirect uptake of viral particles contained inside extracellular vesicles. [45][46][47][48]…”
Section: P Otential Recep Tor S For Sar S -Cov-2 B Ind Ing To Meg Amentioning
confidence: 99%
“…In addition to direct virus interaction with megakaryocytes and platelets, it is possible SARS-CoV-2 virus released into extracellular vesicles from infected white blood cells or endothelial cells can be internalized by platelets, resulting in SARS-CoV-2 virus positive platelets through indirect uptake of viral particles contained inside extracellular vesicles. [45][46][47][48]…”
Section: P Otential Recep Tor S For Sar S -Cov-2 B Ind Ing To Meg Amentioning
confidence: 99%
“…These EVs have the potential to modulate biologic processes distal from the site of platelet activation [47,48]. So far, platelet-derived EVs have been demonstrated to enhance the recruitment of monocytes and neutrophils to the vessel wall during inflammation [49,50]; deposit chemokines that trigger the recruitment of monocytes [51]; directly promote monocyte differentiation into macrophages [52]; alter macrophage genotype and function [53,54]; induce proliferation and transformation of smooth muscle cells to a pro-inflammatory phenotype [55]; upon infiltrating the bone marrow, modulate the behavior of megakaryocytes to alter thrombopoiesis during inflammation [56]. Although these observations might be explained by the action of proteins and lipids carried by EVs, a number of interesting studies have also pointed towards nucleic acids, notably microRNAs (miR), as molecular effectors.…”
Section: Release Of Extracellular Vesicles and Mirna Transfermentioning
confidence: 99%
“…Alternatively, recent studies have shown that aaRSs can be secreted via exosomes, and therefore we cannot exclude the possibility that YRS is present in such vesicles in plasma 27 . Interestingly, it has recently been reported that platelet‐derived extracellular vesicles (PEVs) infiltrate the bone marrow during inflammation and provide direct communication of plasma components with bone marrow cells 28 . It is possible that PEVs contain active form of endogenous YRS protein (eg, YRS Mini+ ) and infiltrate the bone marrow, where it stimulates megakaryopoiesis under inflammatory stress conditions.…”
Section: Discussionmentioning
confidence: 96%